Enhancing wear resistance of R220 rail steels by quenching and partitioning (Q&P) treatment - Gecu, Ridvan (ELSEVIER, 2024)
In this study, R220 steels were subjected to the Q&P treatment after austenitization at 900 degrees C for 15 min. The austenitized samples were immersed in cold, warm, and boiled water baths. The quenching step was interrupted, and the specimens were immediately placed in a furnace at 500 degrees C and held there for 5 min. The multiphase structure, including tempered martensite, retained austenite, bainitic ferrite, and fresh martensite, was achieved by the Q&P treatment. The wear rate of the untreated R220 rail steel was decreased by up to 89 % with a slight increase in corrosion losses. The best wear resistance was obtained in the sample cooled in warm water due to the balance between its tensile strength, toughness, and hardness.
Keywords: Wear and tribology; Corrosion; Microstructure; Metals and alloys; Materials Science; Physics